Hubungan Berat Badan Terhadap Enhancement Hepar Pada Pemeriksaan CT Scan Abdomen 3 Fase Pada Pasien Dengan Klinis Hepatocellular Carcinoma - Mahfud Edy Widiatmoko (JURNAL TERAS KESEHATAN, 2025)
Enhancement of the liver on CT Scan of the abdomen, 3 phases. Influenced by various factors, one of which is body weight. Body weight shows an inverse relationship of one to one with contrast enhancement. Body weight shows an inverse relationship of one-to-one with contrast enhancement. Body weight affects the level of enhancement in the vascular and parenchymal areas. Contrast media is more dilute when administered to patients with larger blood volumes and higher body weights compared to thinner patients. This results in reduced contrast concentration in the blood and lower contrast enhancement. This study aims to analyze the relationship between body weight and liver enhancement in 3-phase abdominal CT scans with clinical hepatocellular carcinoma. The study design is an analytical quantitative study using Pearson's correlation test on the average HU values of the liver from three body weight groups. The study was conducted at Persahabatan Hospital from January to May 2024 with 30 samples using purposive sampling. The results showed that the hepatic enhancement value with p-value 0.000 and r-value -0.612 for arterial phase and p-value 0.000 and r-value -0.629 for venous phase. Conclusion: Body weight is inversely related to hepatic enhancement, if body weight increases,